Pengaruh Penggunaan E-Learning Quipper School Terhadap Minat Belajar Siswa Pada Mata Pelajaran Matematika Kelas XII Pada SMAN 2 Kuala Kapuas - Riri Wijaya Kusuma; Purnomo, Widiharto; Winaryo, Slamet (FKIP Universitas Palangka Raya, 2025)
E-Learning is an innovation in education that has a very large contribution to changes in the learning process, where the learning process is not only limited to lecture activities with simple media but the delivery of learning materials can be visualized in various formats and forms that are more dynamic and more interactive so that students will be more motivated. SMAN 2 Kuala Kapuas is one of the schools that provides Quipper School services for students from grades X to XII. Quipper School provides two services for its users, namely free and paid services. Lack of achievement of mathematics material received by students at school, then students prefer to use the paid service Quipper School to facilitate understanding in absorbing Mathematics material. The method used in this study uses a quantitative research type because it tests the hypothesized theory. Using primary data through questionnaires. Hypothesis testing uses simple linear regression data analysis techniques assisted by using the SPSS version 26 program application. The results of E-Learning Quipper School research on student interest in learning, it can be concluded that the constant value of student interest in learning (Y) is 28.484 and if the value of E-Learning Quipper School increases by 1% then variable Y will increase by 0.348 so that E-Learning Quipper School has a positive impact of 19.5% on student interest in learning Class XII SMAN 2 Kuala Kapuas.